2018
DOI: 10.1007/s10517-018-4039-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper Dyshomeostasis in the Pathogenesis of Parkinson’s Disease

Abstract: Serum concentration of copper, immunoreactive polypeptides of ceruloplasmin and its oxidase activity, and the number of copper atoms per ceruloplasmin molecule were decreased in patients with Parkinson's disease in comparison with the corresponding parameters in age-matched healthy individuals, but the ratio of apoceruloplasmin to holoceruloplasmin in patients with Parkinson's disease was similar in both groups. Treatment of blood serum with Helex 100, a high-affinity copper chelator, revealed reduced content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Copper dyshomeostasis, manifested as an alteration of copper status indices, is not a mandatory feature of PD. Previously, we screened a cohort of 50 PD patients and only revealed 17 patients with copper status indices that were characteristic of heterozygous WD carriers [83], but our experience still indicates that copper status observation in PD patients is sensible. The timely detection of a heterozygous WD gene in patients with PD clinical symptoms and the prescription of chelation therapy may help to slow down or even prevent PD development.…”
Section: Discussionmentioning
confidence: 99%
“…Copper dyshomeostasis, manifested as an alteration of copper status indices, is not a mandatory feature of PD. Previously, we screened a cohort of 50 PD patients and only revealed 17 patients with copper status indices that were characteristic of heterozygous WD carriers [83], but our experience still indicates that copper status observation in PD patients is sensible. The timely detection of a heterozygous WD gene in patients with PD clinical symptoms and the prescription of chelation therapy may help to slow down or even prevent PD development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, albumin takes part in the transport of copper [ 112 ]. Copper is a cofactor of many enzymes and a participant in redox reactions and signaling pathways in the body in normal and pathological states [ 113 ]. The main binding site of Cu(II) cations is the N-terminal site (NTS) of HSA Asp-Ala-His-Lys [ 114 ].…”
Section: Redox Modulation and Redox Activity Of Albuminmentioning
confidence: 99%
“…The potentiation between copper and iron in Parkinson disease patients was proved in cerebrospinal fl uid as well (104). Another study reported that number of copper ions bound on one molecule of ceruloplasmin was reduced in patients suffering from Parkinson disease (105). Using a model comprising laboratory rats, symptoms of Parkinson disease and damaging of the pars compacta of substantia nigra was initiated by administered copper (106).…”
Section: Alzheimer Disease and The Other Neurodegenerationsmentioning
confidence: 98%